Pengaruh Web Service Quality, Customer Satisfaction Dan Behavioural Intention: Attitude Towards The Website Sebagai Variabel Intervening (Study Pada Mahasiswa Universitas Negeri Padang) - Nia Liza Tania; Abror Abror (Universitas Negeri Padang, 2019)
This study analyzes: (1)the effect of web service quality on attitude towards the website, (2) The effect of customer satisfaction on attitude towards the website, (3) The effect of web service quality on behavioural intention, (4) the effect of customer satisfaction on behavioural intention, (5) the effect of attitude towards the website on behavioural intention, (6) the effect of web service quality on customer satisfaction.This type of research is causative research. The population in this study was all students from Padang State University who used the Olx online shop. By using purposive sampling we use 180 customers as the respondent. This study used online questionnaires as the data collection instrument, This study analyzed the data by using structural equation modeling (SEM) with smart PLS 3.0 as the software package.The results of this study indicate that: (1) web service quality has a significant effect on attitude towards the website. (2) customer satisfaction has a significant effect on attitude towards the website. (3) web service quality has a significant effect on behavioural intention. (4) customer satisfaction has a significant effect on behavioural intention. (5) attitude towards the website has a significant effect on behavioural intention. (6) web service quality has a significant effect on customer satisfaction. Keywords:web service quality, attitude towards the website, customer satisfaction, behavioural intention